Mediating Role of Financial Development in Association between Economic Policy Uncertainty and Household Financial Vulnerability: Insights from Upper- and Middle-Income Countries - Chughtai, Qudsia Fatima; Rashid, Abdul (Journal of Innovative Research in Management Sciences, 2026)
Purpose—The study examines the impact of economic policy uncertainty (EPU) on Household Financial Vulnerability (HFV) and examines how financial inclusion (FIN), financial efficiency (FE), financial stability (FS), and financial depth (FDP) mediate this relationship. Study Design/methodology/approach— A composite HFV index is developed using Principal Component Analysis (PCA) to evaluate the differential effect of EPU on HFV. The two-step System Generalized Method of Moments (GMM) estimator estimates the impact of EPU on HFV across a panel of 28 upper- and middle-income countries (UIC and MICs) from 2000 to 2021. Panel Structural Vector Auto-Regressive Model (PSVAR) validates the robustness of the estimation results. The bootstrap test assesses the indirect effects of financial development (FDV). Findings—The findings reveal that EPU is a key driver of HFV, and the differential analysis reveals that MICs are more vulnerable to EPU. All dimensions of FDV buffers households against EPU while partially mediating EPU’s effects on HFV, although the strength of this transmission differs across country groups. The Mediation path is broader in MICs, and FE fully mediates the impact of EPU in MICs. The mediation path is narrow in UICs where FS and FE significantly mediate the impact of EPU on HFV, while FIN and FDP do not confirm a significant mediation path. Practical Implications—Theoretically, the study provides a comprehensive understanding of existing consumer behavior models under uncertainty, particularly across countries at different levels of economic and financial development. It offers policymakers valuable insights for formulating and evaluating targeted programs to improve household well-being through a resilient financial infrastructure. The study provides practical guidance for households to mitigate risks associated with policy uncertainty and to enhance understanding of household financial management. Originality/Value— First, the study contributes contextually by examining the differential impact of EPU on HFV across MICs and UICs. Secondly, the study explores the transmission pathways of EPU by considering the mediating effects of different dimensions of FDV on the relationship between EPU and HFV. The heterogeneity analysis increases the credibility of the research by showing that the EPU–HFV nexus structurally depends on the level of economic and financial development rather than being uniform across economies.